Activation of miR165b represses AtHB15 expression and induces pith secondary wall development in Arabidopsis. (24th June 2015) - Du, Qian; Avci, Utku; Li, Shengben; Gallego‐Giraldo, Lina; Pattathil, Sivakumar; Qi, Liying; Hahn, Michael G.; Wang, Huanzhong
Summary Secondary cell‐wall thickening takes place in sclerenchyma cells, but not in surrounding parenchyma cells. The molecular mechanism of switching on and off secondary wall synthesis in various cell types is still elusive. Here, we report the identification of a dominant mutant stp–2d showing secondary wall thickening in pith cells (STP). Immunohistochemistry assays confirmed accumulation of secondary cell walls in the pith cells of the stp–2d mutant. Activation of microRNA 165b (miR165b) expression is responsible for the STP phenotype, as demonstrated by transgenic over‐expression experiments. The expression of three class III HD–ZIP transcription factor genes, including AtHB15, was repressed in the stp–2d mutant. Transgenic over‐expression of a mutant form of AtHB15 that is resistant to miR165‐mediated cleavage reversed the stp–2d mutant phenotype to wild‐type, indicating that AtHB15 represses secondary wall development in pith. Characterization of two athb15 mutant alleles further confirmed that functional AtHB15 is necessary for retaining primary walls in parenchyma pith cells. Expression analyses of cell‐wall synthetic genes and wall‐related transcription factors indicated that a transcriptional pathway is involved in AtHB15 function. These results provide insight into the molecular mechanism of secondary cell‐wall development.